Membangun Konstruksi Keilmuan Ekonomi Islam - Sanrego Nz, Yulizar D. (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
Theories of Islamic economics have formed part and parcel of the global study on economy. Practically on the other hand, Islamic economics have shown its competing ability andreceived in turn a cheerful welcome from the business community as well as from the masses at the global stage. This paper is an attempt to make a contribution in the field of what we may call the scientific construction of Islamic economics. The paper proposes that this science consists of two aspects, namely value and knowledge. With regards to the latter, on which this paper will pay its major attention, the role of methodology is crucial. This paper will therefore touch on this issue and the role of methodology in inventing knowledge and in the analysis of economic datum. Here by methodology we mean particularly fiqh. We contend that fiqh is in itself methodology. It is rich with methodological tools such as the concept of maqashid al-syariah (the purpose of divine law) which may be used not only to analyze economic datum but also to provide a schemata in resolving some economic problems. By speaking of fiqh as a science of economics we hope to pave the way for the possible invention of the science of economics based on fiqh and its philosophy.